Studi PerbandinganKemampuan Membaca Al-Qur'an Anak-Anak Desa Pidoli Lombang Kab. Madina dengan Menggunakan Metode Iqra dan Metode Al-Barqy - Nurhayani Nurhayani (Al-Murabbi: Jurnal Pendidikan Islam, 2023)
This research is about a comparative study of children's ability to read the Koran in Pidoli Lombang Madina village using the lqra' method and al-Barqy method, to find out how much children's ability to read the Koran uses the iqra method. al-barqy and wanted to know how the comparison speed of children's Al-Quran reading abilities using the igra method with the al-barqy method in Pidoli Lombang Village, Madina Regency. The data collected was classified into qualitative and quantitative data. Meanwhile, to prove the hypothesis of this research, statistical analysis is used here, namely the "t" test. Based on the description above, the results of this research show that the reading ability of children taught using the IQA method tends to be moderate. This is evident from the average score obtained by children of 47.58 and a standard deviation of 8.48. Likewise, the reading ability using the al-Barqy method is on average where the average score obtained by respondents is 54 with standard deviation of 10.32 The reading ability of children taught using the iqra' and al-bargy methods has a significant difference. This is revealed by obtaining a calculated 't' value that is greater than the table (2.25 2.0). Seeing the differences and based on the score obtained for the two eTbook methods, the reading ability using the al-barqy method is superior to using the iqra method.